In-vitro applications of swertiaxanthone extracts on callus growth - VIJAY DAMODHAR MENDHULKAR; ARUNA SHAHAJI NANGARE (International Journal of Pharma and Bio Sciences, 2017)
Swertia species are important botanical sources of xanthones. These compounds have remarkable pharmacological properties such as antipyretic, hypoglycaemic, anti-carcinogenic, antihepatoxic, antimicrobial and antiviral. Xanthones-rich extracts have been widely used for the treatment of various health ailments and used in nutritional supplements, herbal cosmetics and pharmaceutical preparations. The purpose of this study is to examine the In-vitro impact of Swertia species crude xanthone extracts on callus growth. Seven xanthone concentrations (5 mg/L, 10 mg/L, 20 mg/L, 40 mg/L, 60 mg/L, 80 mg/L and 100 mg/L.) were prepared from three Swertia species i.e. Swertia densifolia, Swertia lawii and Swertia minor. Leaf callus was grown in xanthone supplemented MS media. Results obtained were recorded in the form of growth parameters, biochemical analysis, protein profiling and cell viability. Media supplemented with Swertia xanthones were able to develop calli from leaf explants. Fresh and dry weight recorded to be high in all S. minor xanthone treated calli, Moisture content was more in many studied xanthone concentrations compared to control (94.36%). From the studied phytochemicals, the polyphenols were accumulated in very high amount. Protein profiling study revealed the expression of low and high molecular weight proteins and the numbers of low molecular weight protein bands were recorded more. S. densifolia xanthone supplemented medium (80 mg/L and 100 mg/L) enhances the expression of more proteins. The cell viability parameter was analysed and it was observed that S. minor xanthone treated cell cultures indicated 97.6% cell viability against control cell viability of 93.21%.